E-module of Plane Figure (EDUNTAR) Based on Culturally Responsive Teaching Approach Assisted by Heyzine Flipbook for Grade IV Elementary Students - Friska Olivia; Yuniawatika; Ferril Irham Muzaki (Universitas Pendidikan Ganesha, 2025)
Many students still face difficulties in learning mathematics, especially in plane geometry materials that require strong visualization skills. To overcome these obstacles, teaching materials are needed that can support the visual representation process and facilitate students' learning needs. This study aims to analyze and develop a plane geometry e-module (EDUNTAR) based on Culturally Responsive Teaching (CRT) using a valid, practical, and effective flipbook format as a learning medium. This research is a development research with the ADDIE model, involving fourth-grade students as trial subjects. Data were collected through interviews, questionnaires, and tests using expert validation instruments, practicality sheets, and learning outcome tests. Data analysis was carried out quantitatively and qualitatively. The validation results showed that EDUNTAR was in the very valid category, with a score of 94.64% from material experts and 97.91% from teaching material experts. The practicality test obtained a score of 100% from teachers and 99.10% from students, indicating a very practical category. The effectiveness test showed that EDUNTAR was able to improve students' understanding of plane geometry materials. Thus, it can be concluded that the EDUNTAR e-module based on the CRT approach is suitable for use, supports a more meaningful learning process, and has the potential to strengthen students' visualization abilities and understanding of mathematical concepts.